Copper-tin alloy heating wire and preparation method thereof

By covering the protective layer of natural polysaccharide material matrix and nano-scale metal oxide particles on the copper-tin alloy heating line, and forming hollow channels inside to fill tea tree essential oil, the problem of shortening service life of traditional heating line due to microbial erosion and biofilm formation is solved, and higher corrosion resistance and heat exchange efficiency are achieved.

CN119822435AInactive Publication Date: 2025-04-15BINHAI PERUI ELECTRONIC TECHNOLOGY CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202510169427.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-02-17
Publication Date
2025-04-15
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

The service life of traditional copper-tin alloy heating wires in sewage treatment equipment is shortened due to microbial erosion and biofilm formation, resulting in increased maintenance costs and reduced sewage treatment efficiency.

Method used

A copper-tin alloy heating wire is used, and its surface is covered with a protective layer composed of a matrix of natural polysaccharide substances and nano-scale copper oxide and zinc oxide particles. A uniform hollow channel distributed along the axial direction is formed inside the heating wire, filled with tea tree essential oil as an antibacterial agent.

Benefits of technology

Effectively prevent microbial adhesion and growth, reduce biofilm formation, significantly improve the corrosion resistance and heat exchange efficiency of the heating wire, extend service life and reduce maintenance costs.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119822435A_ABST
    Figure CN119822435A_ABST
Patent Text Reader

Abstract

The invention discloses a copper-tin alloy heating wire and a preparation method thereof, and relates to the technical field of heating wire preparation, the copper-tin alloy heating wire comprises a heating wire used for heating sewage treatment equipment, the heating wire is made of copper-tin alloy, and a plurality of uniform hollow channels which are distributed in the axial direction and have the diameter of 2 microns are formed in the heating wire; according to the invention, the protective layer is composed of a natural polysaccharide substance matrix and nanoscale copper oxide and zinc oxide particles, the protective layer physically obstructs microorganisms and the natural polysaccharide substance matrix and the nanoscale copper oxide and zinc oxide particles synergistically resist bacteria, and meanwhile, tea tree essential oil filled in an internal hollow channel volatilizes during heating to form a dynamic antibacterial protective film, so that the adhesion amount of the microorganisms is greatly reduced, and the service life is prolonged; a protective layer and an antibacterial agent inhibit the formation of a biological membrane and reduce thermal resistance, and a hollow channel in a heating wire promotes heat conduction, so that the temperature of sewage is increased more quickly and uniformly, and the yield and quality of biogas are also improved; and the natural polysaccharide substance matrix of the protective layer is prepared from waste rice straws, so that the resource utilization of wastes is realized, the cost is reduced, and the environment is protected.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of heating wire preparation, in particular to a copper-tin alloy heating wire and a preparation method thereof. Background Art

[0002] In sewage treatment equipment, the copper-tin alloy heating wires used for heating are in a complex microbial environment for a long time and face many serious problems.

[0003] In the sewage treatment system, microorganisms such as sulfur-oxidizing bacteria play a key role in the growth and metabolism process. When sulfur-oxidizing bacteria metabolize sulfur-containing compounds, they produce acidic substances such as sulfuric acid. According to the chemical reaction principle of metals and acids, sulfuric acid will react with the metal on the surface of the heating wire, causing the metal components to dissolve, causing pits and thinning to gradually appear on the surface of the heating wire, which will seriously affect the mechanical strength and electrical properties of the heating wire. In addition, some acid-producing bacteria will also produce organic acids during the metabolism process, and these organic acids will also cause corrosion to the surface of the heating wire.

[0004] At the same time, some microorganisms with special enzyme activities, such as some oxidase-producing bacteria in iron-oxidizing bacteria, can catalyze the redox reaction on the surface of the heating wire. According to the catalytic principle of enzymes, these enzymes can reduce the activation energy of the redox reaction and accelerate the oxidation process of metals. Taking iron-oxidizing bacteria as an example, it can oxidize the metallic iron on the surface of the heating wire, forming a layer of oxide film with poor conductivity on the surface of the heating wire, thereby increasing resistance and reducing heating efficiency.

[0005] Furthermore, the biofilm formed by the attachment and growth of microorganisms on the surface of the heating wire also brings many problems. From the perspective of heat transfer and electrochemistry, the thermal conductivity of the biofilm is low, which greatly hinders the transfer of heat from the heating wire to the sewage and reduces the heat exchange efficiency. There are many kinds of microorganisms in the biofilm, such as sulfate-reducing bacteria. In the microenvironment inside the biofilm, sulfate-reducing bacteria will use the microbial metabolites and various electrolytes rich in the biofilm to form an environment similar to a primary battery. In this microenvironment, sulfate-reducing bacteria will accelerate the corrosion process of the heating wire, making the corrosion of the heating wire more serious.

[0006] At present, the research on the performance changes of materials in microbial environments mainly focuses on the field of corrosion-resistant materials, and there is a relative lack of research on the performance degradation of functional materials such as copper-tin alloy heating wires in microbial environments. In addition, the interaction mechanism between microorganisms and materials is extremely complex, involving multidisciplinary knowledge such as microbiology, materials science, and chemistry. Exploring this direction is innovative and challenging.

[0007] Due to the existence of the above problems, the service life of traditional heating wires in sewage treatment equipment is greatly shortened. Frequent replacement of heating wires not only increases maintenance costs, but also affects the continuity of sewage treatment due to downtime maintenance, reducing sewage treatment efficiency. Therefore, it is of great practical significance and urgency to develop a copper-tin alloy heating wire that can effectively resist microbial erosion and improve heat exchange efficiency and a preparation method thereof, which is also the key problem that the present invention is committed to solving.

[0008] In view of this, a copper-tin alloy heating wire and a preparation method thereof are provided to overcome the above problems. Summary of the invention

[0009] The object of the present invention is to provide a copper-tin alloy heating wire and a preparation method thereof to solve the problems raised in the above background technology.

[0010] In order to solve the above technical problems, the present invention provides a copper-tin alloy heating wire, including a heating wire for heating sewage treatment equipment. The material of the heating wire is copper-tin alloy, and the interior of the heating wire is provided with a plurality of uniform hollow channels distributed along the axial direction and with a diameter of 2 microns; the surface of the heating wire is covered with a protective layer, and the protective layer is composed of a natural polysaccharide material matrix and nano-scale copper oxide and zinc oxide particles uniformly dispersed therein.

[0011] Furthermore, the mass ratio of copper oxide to zinc oxide is 2.5:1.

[0012] Furthermore, the natural polysaccharide material matrix of the protective layer is prepared by hydrolysis and polymerization of discarded rice straw.

[0013] Further, a hollow channel is formed inside the copper-tin alloy heating wire by a drawing die.

[0014] A method for preparing a copper-tin alloy heating wire comprises the following steps: Preparation of protective layer materials: Collect discarded rice straw and wash it with a cleaning device equipped with high-pressure water spray and rotating brush. The high-pressure water spray pressure is controlled at 5-8MPa and the rotating brush speed is 100-150 rpm. After washing, use a high-speed crusher to crush it into uniform fragments with a particle size range of 2-5 mm. Hydrolysis reaction: The crushed straw fragments are transferred to a reactor equipped with a precise temperature control system and a stirring device, and a sulfuric acid solution with a mass fraction of 8% is added. The mass ratio of straw fragments to sulfuric acid solution is 1:5-1:8. The reaction temperature is precisely controlled at 85°C, the stirring device speed is 150-200 rpm, and the reaction time is 2.5 hours. Polymerization reaction: After the hydrolysis reaction is completed, cool to 55°C at a cooling rate of 5-8°C / min, add an appropriate amount of glutaraldehyde crosslinking agent, and add glutaraldehyde in an accurately calculated stoichiometric ratio of 1:2-1:3 to the active groups in the hydrolyzate. Stir at a low speed of 50-60 rpm for 3-4 hours in a constant temperature water bath environment; Mixing of nano-sized metal oxide particles: using a high-precision electronic balance with an accuracy of 0.0001 g, weigh nano-sized copper oxide and zinc oxide particles respectively in a copper oxide to zinc oxide mass ratio of 2.5:1, add them to the prepared natural polysaccharide matrix, and transfer to an ultrasonic dispersion device; Heating wire coating: Select the copper-tin alloy heating wire prepared in advance according to the heating performance requirements, pour the protective layer precursor solution into the corrosion-resistant polytetrafluoroethylene coating tank, and use the pulling method to coat it at a pulling speed of 1 cm / s. After coating twice, dry it in a low-temperature drying oven set at 45°C for 1.5 hours; Hollow channel formation: A hollow channel is formed inside the copper-tin alloy heating wire using a drawing die and a drawing process. The drawing die is made of cemented carbide material, and the shape and size accuracy of the internal channel is controlled within ±0.01mm; Antimicrobial filling: Tea tree essential oil is selected as the volatile antimicrobial agent and injected into the hollow channel through a high-precision microinjection pump. The injection pressure is controlled at 0.5-1MPa. The injection volume is calculated based on the volume of the hollow channel and the concentration of the tea tree essential oil. After the injection is completed, a water-resistant, temperature-resistant and well-adhesive epoxy resin sealant is used to seal both ends of the channel.

[0015] Furthermore, before the protective layer raw material preparation step, the heating power demand of the sewage treatment equipment is analyzed, the actual working conditions of the sewage treatment equipment are simulated multiple times, and the resistance value and heating power of the heating wire under different copper-tin ratios are measured using a resistance-temperature testing device to determine the ratio of copper to tin in the copper-tin alloy heating wire.

[0016] Furthermore, in the step of mixing the nano-sized metal oxide particles, the ultrasonic frequency is set to 40-60 kHz, the ultrasonic power is 250 W, and the ultrasonic dispersion time is 35 minutes.

[0017] Furthermore, during the drawing process of hollow channel formation, the drawing force and the drawing speed are monitored in real time by high-precision sensors, and the control system automatically adjusts the drawing parameters to control the drawing force to be stable at 10-15 kN and the drawing speed to be controlled at 0.5-1 m / min.

[0018] Compared with the prior art, the present invention has the following beneficial effects: The protective layer on the surface of the heating wire is composed of a natural polysaccharide matrix and nano-scale copper oxide and zinc oxide particles, which can physically block microorganisms. Its antibacterial properties can also inhibit the attachment and growth of microorganisms, greatly reducing the amount of microorganisms attached to the surface of the heating wire, reducing the possibility of biofilm formation, and preventing the heating wire from being corroded; the tea tree essential oil filled in the hollow channel inside the heating wire evaporates to the surface when the working temperature rises to form a dynamic antibacterial protective film, which continuously inhibits the growth and attachment of microorganisms and extends the service life of the heating wire. Its service life in sewage treatment equipment is 3-5 times that of traditional heating wires.

[0019] The protective layer and antibacterial agent inhibit the formation of biofilm, reduce the thermal resistance of heat exchange, shorten the time for sewage to heat up to the set temperature, make the heating rate more stable, and the temperature distribution more uniform; the hollow channel inside the heating wire is conducive to heat conduction and diffusion, improves the heat conduction efficiency, makes the temperature of the anaerobic fermentation tank quickly and evenly reach and maintain the appropriate range, promotes the conversion of organic matter into biogas, and increases the biogas production by about 15%-20%.

[0020] The natural polysaccharide material matrix of the protective layer is prepared from discarded rice straw, which realizes the resource utilization of waste, reduces procurement costs, and alleviates the pressure on the environment caused by improper straw treatment. BRIEF DESCRIPTION OF THE DRAWINGS

[0021] Figure 1 The schematic diagram of a copper-tin alloy heating wire and a preparation method thereof of the present invention is shown. DETAILED DESCRIPTION

[0022] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0023] See also Figure 1 , the present invention provides a technical solution: See also Figure 1 As shown, an embodiment of a copper-tin alloy heating wire and a method for preparing the same: Application Scenario In a sewage treatment plant in a medium-sized city, the anaerobic treatment process is the core link of the sewage purification process. It mainly relies on a group of large anaerobic fermentation tanks to realize the conversion of organic matter in sewage into usable resources such as biogas. Microorganisms are extremely sensitive to temperature changes during anaerobic fermentation. After a large number of experimental studies and actual operation data, it is shown that when the temperature is 35-38℃, the enzyme activity of microorganisms is the strongest and the metabolic rate is the fastest, which can ensure stable and efficient fermentation efficiency, thereby achieving full decomposition of organic matter and maximizing the output of biogas.

[0024] The traditional heating method uses ordinary metal heating wires, which have many serious problems after being in a complex microbial environment for a long time. From the perspective of microbial metabolism, microorganisms secrete a variety of metabolites during their growth. Some of these acidic substances, such as sulfuric acid and hydrochloric acid, are produced by specific microorganisms when metabolizing sulfur-containing and chlorine-containing compounds. These acidic substances will react chemically with the metal on the surface of the heating wire, following the principle of chemical reaction between metal and acid, causing the metal components to dissolve, causing pits and thinning on the surface of the heating wire, and other corrosion phenomena, which in turn affects the mechanical strength and electrical properties of the heating wire.

[0025] At the same time, some microorganisms with special enzyme activities, such as some oxidase-producing bacteria, will catalyze the redox reaction on the surface of the heating wire. According to the catalytic principle of enzymes, these enzymes can reduce the activation energy of the redox reaction, accelerate the oxidation process of the metal, and form a layer of oxide film with poor conductivity on the surface of the heating wire, thereby increasing resistance and reducing heating efficiency.

[0026] In addition, the biofilm formed by the attachment and growth of microorganisms on the surface of the heating wire has a low thermal conductivity from the perspective of heat transfer and electrochemistry, which hinders the transfer of heat from the heating wire to the sewage and reduces the heat exchange efficiency. Moreover, the biofilm is rich in microbial metabolites and various electrolytes, forming a microenvironment similar to a galvanic cell, which accelerates the corrosion process of the heating wire.

[0027] The above problems lead to a significant shortening of the service life of the heating wire. Frequent replacement of the heating wire not only increases the maintenance cost, but also affects the continuity of sewage treatment due to downtime for maintenance, thereby reducing the sewage treatment efficiency. The copper-tin alloy heating wire and the preparation method thereof of the present invention are intended to effectively solve these problems.

[0028] Preparation steps of copper-tin alloy heating wire Preparation of protective layer materials: Collect discarded rice straw around the city. Most of these straws are randomly discarded or burned after agricultural production, which not only causes environmental pollution but also wastes potential resources. Use professional industrial cleaning equipment, such as a cleaning device with high-pressure water spray and rotating brush. The high-pressure water spray pressure is controlled at 5-8MPa and the rotating brush speed is 100-150 rpm to clean the collected straw. Then, use a high-speed crusher with a crushing speed of 3000-5000 rpm to crush the cleaned straw into uniform fragments with a particle size range of 2-5 mm.

[0029] Rice straw was chosen because it is widely available and rich in polysaccharides such as cellulose, making it an ideal raw material for preparing natural polysaccharide matrices. The setting of the high-pressure water spray pressure and the rotating brush speed is based on the consideration of the adhesion of common pollutants on the surface of the straw and the performance of the cleaning equipment. It can effectively remove pollutants such as soil and impurities without causing excessive damage to the straw. The crushing speed is selected to crush the straw into a suitable particle size for the subsequent hydrolysis reaction. This particle size range can not only ensure the sufficiency of the hydrolysis reaction, but also facilitate subsequent processing.

[0030] It realizes the resource utilization of waste, reduces the procurement cost of protective layer raw materials, and reduces the pressure on the environment caused by improper straw treatment, which has significant environmental benefits.

[0031] Hydrolysis reaction: The crushed straw fragments are transferred to a reactor equipped with a precise temperature control system and a stirring device. The reactor is made of corrosion-resistant stainless steel, the temperature control system has an accuracy of ±0.5°C, and the stirring device is a paddle stirrer. Add 8% sulfuric acid solution by mass, and the amount of sulfuric acid solution is added according to the mass ratio of straw fragments to sulfuric acid solution of 1:5-1:8. During the reaction process, the reaction temperature is precisely controlled at 85°C by the temperature control system, and the stirring device is used to continuously stir at a speed of 150-200 rpm, and the reaction time is set to 2.5 hours.

[0032] The corrosion-resistant stainless steel reactor was selected because ordinary materials are easily corroded in a dilute sulfuric acid solution environment, which affects the reaction and the life of the equipment. The accuracy of the temperature control system and the choice of the stirring device are to ensure that the hydrolysis reaction is carried out under stable temperature and good mixing conditions. The concentration of sulfuric acid solution with a mass fraction of 8% and the mass ratio of straw fragments to sulfuric acid solution are the optimal reaction conditions obtained after a large number of experiments. They can ensure the effective hydrolysis of polysaccharides without causing side reactions due to excessive acidity. The setting of reaction temperature, stirring speed and time is based on the study of the hydrolysis kinetics of polysaccharides such as cellulose and hemicellulose under the catalysis of dilute sulfuric acid. Under these conditions, the hydrolysis reaction can be carried out fully and efficiently.

[0033] Strictly controlling the hydrolysis conditions effectively improved the decomposition efficiency of the polysaccharide, and obtained high-quality hydrolyzate suitable for preparing the protective layer matrix, providing high-quality basic raw materials for the subsequent formation of the matrix with a three-dimensional network structure.

[0034] Polymerization reaction: After the hydrolysis reaction is completed, the cooling circulating water system is used to cool the hydrolyzate in the reactor to 55°C, and the cooling rate is controlled at 5-8°C / minute. Then, an appropriate amount of glutaraldehyde crosslinking agent is added. The amount of glutaraldehyde added is accurately calculated and added according to the stoichiometric ratio with the active groups (such as hydroxyl, carboxyl, etc.) in the hydrolyzate. The content of the active groups in the hydrolyzate is determined by chemical titration, and then the amount of glutaraldehyde added is determined according to the reaction ratio of glutaraldehyde to the active groups (generally 1:2-1:3). In a constant temperature water bath environment, stir at a low speed of 50-60 rpm for 3-4 hours to allow the small molecular sugars in the hydrolyzate to undergo polymerization under the action of glutaraldehyde.

[0035] The control of cooling rate is to prevent the hydrolysis product from being locally uneven due to a sudden drop in temperature, which would affect the subsequent polymerization reaction. Glutaraldehyde is a crosslinking agent, and its reaction with the active groups in the hydrolysis product is the key to constructing a three-dimensional network structure. Accurately determining the content of active groups by chemical titration and adding glutaraldehyde according to the appropriate reaction ratio can ensure that the crosslinking reaction is fully carried out to form a stable three-dimensional network structure. The setting of the constant temperature water bath environment and low-speed stirring is to provide a mild and uniform reaction environment, which is conducive to the orderly crosslinking reaction between molecules.

[0036] The formation of a natural polysaccharide matrix with a three-dimensional network structure gives the protective layer good physical strength and stability, and provides a stable carrier framework for the subsequent addition of nano-scale metal oxide particles.

[0037] Nano-sized metal oxide particles mixed: According to the precise ratio of copper oxide to zinc oxide mass ratio of 2.5:1, nano-scale copper oxide and zinc oxide particles were weighed respectively using a high-precision electronic balance with an accuracy of 0.0001g. The weighed particles were added to the prepared natural polysaccharide matrix, and then transferred to an ultrasonic dispersion device, the ultrasonic frequency of the ultrasonic dispersion device was set to 40-60kHz, the ultrasonic power was 250W, and the ultrasonic dispersion time was 35 minutes.

[0038] The determination of the mass ratio of copper oxide to zinc oxide is based on a large number of antibacterial and anti-corrosion performance test experiments. At this ratio, the synergistic effect of the two can maximize the ability of the protective layer to resist microorganisms and their secretions. The high-precision electronic balance can ensure the accuracy of the weighed nano-scale metal oxide particles, thereby ensuring the accuracy of the mixing ratio. The setting of ultrasonic frequency, power and dispersion time is based on the dispersion characteristics of nano-scale particles in the matrix. Under this condition, the nano-scale metal oxide particles can be evenly dispersed in the matrix to form a stable dispersion system.

[0039] Nano-scale copper oxide and zinc oxide have excellent antibacterial and anti-corrosion properties. After being evenly dispersed in the matrix, the two work synergistically to greatly enhance the protective layer's ability to resist microorganisms and their secretions.

[0040] Heating wire coating: A copper-tin alloy heating wire prepared in advance according to the heating performance requirements is selected. Its copper-tin ratio has been accurately calculated and experimentally verified. The actual working conditions of the sewage treatment equipment are simulated many times, and the resistance value and heating power of the heating wire under different copper-tin ratios are measured using a resistance-temperature test device to finally determine the appropriate copper-tin ratio. The protective layer precursor solution is poured into a specially designed coating tank made of corrosion-resistant polytetrafluoroethylene. The copper-tin alloy heating wire is slowly immersed in the solution and coated by the pulling method. The pulling speed is controlled to 1 cm / s by a high-precision mechanical transmission device. After coating twice, the heating wire is placed in a low-temperature drying oven set at 45°C and dried for 1.5 hours.

[0041] The copper-tin ratio is determined by simulating actual working conditions and resistance-temperature tests to ensure that the heating wire can meet the heating power requirements of the sewage treatment equipment and ensure stable heating in a complex sewage treatment environment. The corrosion-resistant polytetrafluoroethylene coating tank is selected because it can resist the corrosion of the protective layer precursor solution and ensure the smooth progress of the coating process. The pulling speed and the number of coating times are determined based on the requirements for the thickness and uniformity of the protective layer. After experimental verification, under this condition, the protective layer can be evenly and firmly covered on the surface of the heating wire. The temperature and time of low-temperature drying are set to fully dry and solidify the protective layer without affecting the internal structure of the heating wire and the performance of the protective layer.

[0042] The protective layer is evenly and firmly covered on the surface of the heating wire, which not only ensures the protective effect of the protective layer against microbial erosion, but also does not have a negative impact on the internal structure and heating performance of the heating wire.

[0043] Hollow channel formation: A specially designed drawing die and advanced drawing process are used to form tiny hollow channels inside the copper-tin alloy heating wire. The internal structure of the drawing die is optimized and made of cemented carbide material. The shape and size accuracy of the internal channel is controlled within ±0.01mm. During the drawing process, the drawing force and speed are monitored in real time by high-precision sensors. The accuracy of the drawing force sensor is ±0.1kN, and the accuracy of the drawing speed sensor is ±0.01m / minute. The data is fed back to the control system. The control system uses a programmable logic controller (PLC). The control system automatically adjusts the drawing parameters to ensure that the drawing force is stable at 10-15 kN and the drawing speed is controlled at 0.5-1m / minute. Finally, a number of uniform hollow channels with a diameter of about 2 microns distributed along the axial direction are formed inside the heating wire.

[0044] The specially designed drawing die and advanced drawing process are designed to accurately form a hollow channel inside the heating wire without destroying the overall structure. The die made of cemented carbide material has high hardness and wear resistance, which can ensure the accuracy and life of the die during the drawing process. The high-precision sensor and the application of the PLC control system are used to monitor and adjust the drawing parameters in real time to ensure that the size and distribution of the hollow channel are uniform. The range setting of the drawing force and the drawing speed is based on the material properties of the copper-tin alloy and the requirements for the forming of the hollow channel. Within this range, the ideal hollow channel can be successfully formed.

[0045] The existence of the hollow channel not only provides space for the subsequent filling of the antibacterial agent, but also facilitates the conduction and diffusion of heat inside the heating wire during the heating process, thereby improving the heat conduction efficiency of the heating wire.

[0046] Antimicrobial filling: Tea tree essential oil is selected as a volatile antibacterial agent and injected into the hollow channel through a precise injection device. The injection device uses a high-precision micro-injection pump, and the injection pressure is controlled at 0.5-1MPa. The injection volume is accurately calculated based on the volume of the hollow channel and the concentration of the tea tree essential oil. After the injection is completed, a high-strength sealant is used to seal both ends of the channel. The sealant is a water-resistant, temperature-resistant epoxy resin sealant with good adhesion.

[0047] Tea tree essential oil was chosen because it has a broad spectrum of antimicrobial activity and has a good inhibitory effect on common microorganisms in sewage treatment environments. The high-precision microinjection pump and the precisely calculated injection pressure and injection volume can ensure that the tea tree essential oil is evenly filled in the hollow channel. The epoxy resin sealant was chosen based on its water resistance, temperature resistance and good adhesion, which can effectively prevent the leakage of the antimicrobial agent and ensure the stability of the antimicrobial agent in the hollow channel.

[0048] Tea tree essential oil has a broad-spectrum antibacterial activity. When the heating wire is working, the temperature rises and causes the tea tree essential oil to volatilize. The volatilized tea tree essential oil diffuses to the surface of the heating wire through the hollow channel, forming a dynamic antibacterial protective film on the surface of the heating wire, which continuously inhibits the growth and attachment of microorganisms on the surface of the heating wire.

[0049] Practical application in sewage treatment equipment Installation and commissioning: The prepared copper-tin alloy heating wire is installed in the heating system of the anaerobic fermentation tank according to the design requirements. The heating wire is evenly distributed on the inner wall of the fermentation tank in a spiral winding manner and connected to the temperature control system and power supply system. During the installation process, tools such as a level and a distance meter are used to ensure that the spacing error of the heating wire in the circumferential direction and the axial direction does not exceed ±5mm. After the installation is completed, the sensor of the temperature control system is calibrated using a standard thermometer to ensure that it can accurately control the temperature in the fermentation tank within the set range, and the temperature control accuracy can reach ±0.5℃.

[0050] The heating wires are evenly distributed in a spiral winding manner to ensure uniform heating, so that the temperature of each area in the fermentation tank can rise evenly, which is conducive to the growth of microorganisms and the fermentation reaction. The level and rangefinder are used to control the spacing error of the heating wires to ensure the uniformity of the distribution of the heating wires and avoid local temperatures being too high or too low due to uneven spacing. The temperature control system sensor is calibrated using a standard thermometer to ensure the accuracy of temperature control and meet the strict requirements of microorganisms for the temperature environment.

[0051] It ensures that the layout of the heating wires is uniform and reasonable, and ensures that the temperature control system can accurately control the temperature in the fermentation tank within the set range, providing a stable temperature environment for anaerobic fermentation.

[0052] Performance monitoring and analysis: Microbial attachment: After the heating wire has been in operation for 1 month, 3 months, and 6 months, sterile sampling tools are used to collect microbial samples from the surface of the heating wire. The sterile sampling tools use sterile cotton swabs and sampling tubes. When sampling, the sterile cotton swab is used to gently wipe the 10-15cm² area on the surface of the heating wire, and then the cotton swab is placed in the sampling tube. The samples are observed and analyzed using a scanning electron microscope (SEM). After the samples in the sampling tube are fixed, dehydrated, and dried, they are placed under a scanning electron microscope to observe the morphology and distribution of the microorganisms. At the same time, combined with the microbial culture counting method, the samples are inoculated into a specific culture medium and cultured in a constant temperature incubator at 30-35°C for 2-3 days, and the types and numbers of attached microorganisms are counted.

[0053] The use of sterile sampling tools and standardized sampling methods can ensure that the collected microbial samples are representative and avoid contamination by external microorganisms. SEM can visually observe the morphology and distribution of microorganisms, and the microbial culture counting method can accurately count the types and numbers of microorganisms. The combination of the two methods can comprehensively evaluate the attachment of microorganisms on the surface of the heating wire. The setting of the culture temperature and time is based on the growth characteristics of common microorganisms in the sewage treatment environment. Under this condition, the microorganisms can fully grow and reproduce, which is convenient for counting and identification.

[0054] The attachment of microorganisms on the surface of the heating wire was accurately monitored, and the results showed that compared with the traditional heating wire, the amount of microorganisms attached to the surface of the heating wire of the present invention was reduced by about 60% after 1 month, about 80% after 3 months, and about 90% after 6 months. This fully proves that the nano-scale metal oxide particles and volatile tea tree essential oil in the protective layer work together, as well as the three-dimensional network structure of the protective layer, effectively inhibit the attachment and growth of microorganisms, and greatly reduce the possibility of biofilm formation.

[0055] Corrosion degree: After the heating wire was in operation for 3 months and 6 months, the corrosion potential and corrosion current of the heating wire were tested using an electrochemical workstation. The three-electrode system was used, with a saturated calomel electrode as the reference electrode, a platinum electrode as the auxiliary electrode, and the heating wire as the working electrode, and the test was carried out in an electrolyte simulating a sewage environment. The electrolyte simulating a sewage environment was prepared according to the main components of actual sewage, and contained electrolytes such as sodium chloride, sodium sulfate, and sodium bicarbonate at a certain concentration.

[0056] The electrochemical workstation can accurately measure the corrosion potential and corrosion current of the heating wire, and a stable electrochemical measurement circuit can be constructed through the three-electrode system. The electrolyte preparation for simulating the sewage environment is to simulate the corrosion of the heating wire in the actual sewage treatment environment as realistically as possible under laboratory conditions, making the test results more reliable.

[0057] The test results show that the corrosion potential of the copper-tin alloy heating wire of the present invention shifted positively by about 150mV after 3 months and by about 250mV after 6 months; the corrosion current decreased by about 70% after 3 months and by about 85% after 6 months. This shows that the protective layer effectively blocks the acidic substances secreted by microorganisms and microorganisms with special enzyme activities from corroding the surface of the heating wire, prevents the occurrence of redox reactions, significantly improves the corrosion resistance of the heating wire, and protects the surface chemical composition and microstructure of the heating wire.

[0058] Heat exchange efficiency: Multiple temperature sensors are evenly arranged in the anaerobic fermentation tank. The temperature sensors use high-precision platinum resistance temperature sensors with an accuracy of ±0.1°C to monitor the temperature distribution of the sewage in the tank in real time. At the same time, the heat exchange efficiency of the heating wire is calculated by recording the power supply of the heating system and the heating time of the sewage.

[0059] Evenly arranging multiple high-precision platinum resistance temperature sensors can comprehensively monitor the temperature distribution of sewage in the fermentation tank and provide accurate data support for evaluating the heat exchange efficiency. The heat exchange efficiency is calculated by recording the power supply and sewage heating time. It is based on the law of conservation of energy and the principle of heat transfer and can intuitively reflect the heat exchange performance of the heating wire.

[0060] After comparison, it was found that after using the heating wire of the present invention, the heating rate of the sewage was more stable and the temperature distribution was more uniform. Under the same heating power, the time for the sewage to heat up to the set temperature using the heating wire of the present invention was shortened by about 20% compared with that using the traditional heating wire. This shows that the formation of biofilm on the surface of the heating wire is effectively suppressed and the heat exchange efficiency is significantly improved. The polygonal cross-sectional shape increases the surface area of ​​the heating wire, further promotes the dissipation of heat, improves the heat exchange efficiency, and ensures the stable progress of the anaerobic fermentation process. Stable and efficient heat exchange enables the temperature in the anaerobic fermentation tank to quickly and evenly reach and maintain in the appropriate range of 35-38°C, providing an optimal living environment for microorganisms. This not only ensures the activity and metabolic rate of microorganisms, but also promotes the efficient conversion of organic matter into biogas, and improves the yield and quality of biogas. According to statistics, after using the heating wire of the present invention, the biogas production is increased by about 15%-20% compared with the use of traditional heating wires, which is of great significance for energy recovery and resource reuse in sewage treatment plants.

[0061] Summarize: Solve the problem of microbial erosion: Use waste plant straw to prepare the natural polysaccharide matrix of the protective layer, combine nano-scale metal oxide particles and volatile antibacterial agents, and construct a multi-level protection system. The protective layer not only physically blocks the direct contact between microorganisms and the surface of the heating wire, but the nano-scale metal oxide particles and volatile antibacterial agents can inhibit the growth and metabolism of microorganisms, effectively resist the erosion of the heating wire by microorganisms and their secretions, prevent the corrosion of acidic substances and the redox reaction catalyzed by special enzyme-active microorganisms, protect the surface structure and chemical composition of the heating wire, and extend the service life of the heating wire. After actual application comparison, the service life of the copper-tin alloy heating wire of the present invention in sewage treatment equipment is 3-5 times that of traditional heating wires, which greatly reduces the replacement frequency and maintenance cost of the heating wire.

[0062] Improved heat exchange efficiency: By inhibiting the formation of biofilm, the thermal resistance in the heat exchange process is reduced, ensuring efficient heat exchange between the heating wire and the surrounding environment. At the same time, the polygonal cross-sectional shape increases the heat dissipation area of ​​the heating wire, further improving the heat exchange efficiency, allowing the sewage to be heated evenly and stably, providing a good temperature environment for anaerobic fermentation, and improving the efficiency of anaerobic fermentation during sewage treatment, thereby improving the treatment capacity of the entire sewage treatment plant. Due to the improvement in heat exchange efficiency, the sewage treatment plant can treat more sewage in the same time, and the treatment capacity has increased by about 20%-30% compared with before, which helps to alleviate the pressure of urban sewage treatment.

[0063] Combination of innovation and practicality: The present invention innovatively integrates multidisciplinary knowledge such as microbiology, materials science and chemistry and applies it to the design and preparation of copper-tin alloy heating wires. A practical and innovative solution is proposed to address the problem of performance degradation of functional materials in microbial environments. This method not only effectively solves the practical problems faced by heating wires in sewage treatment equipment, but also has the advantages of low cost and environmental protection. It provides new ideas and references for the research and development of other functional materials used in complex environments, and has broad application prospects and promotion value. At present, this technology has been successfully applied in multiple anaerobic fermentation tanks in this medium-sized urban sewage treatment plant, and has achieved good results. It is expected to be promoted in more sewage treatment plants and other application scenarios in similar complex environments.

[0064] In summary, the copper-tin alloy heating wire and the preparation method thereof of the present invention have demonstrated excellent performance and significant advantages in the practical application of sewage treatment equipment, providing strong technical support for the development of the sewage treatment industry.

Claims

1. A copper-tin alloy heating wire, including a heating wire for heating sewage treatment equipment, characterized in that: The heating wire is made of copper-tin alloy, and the inside of the heating wire is provided with a number of uniform hollow channels with a diameter of 2 microns distributed along the axial direction; the surface of the heating wire is covered with a protective layer, which is composed of a natural polysaccharide matrix and nano-scale copper oxide and zinc oxide particles uniformly dispersed therein.

2. A copper-tin alloy heating wire as claimed in claim 1, characterized in that: The mass ratio of copper oxide to zinc oxide is 2.5:

1.

3. The copper-tin alloy heating wire according to claim 1, characterized in that: The natural polysaccharide material matrix of the protective layer is prepared from discarded rice straw through hydrolysis and polymerization reaction.

4. The copper-tin alloy heating wire according to claim 1, characterized in that: The hollow channel is formed inside the copper-tin alloy heating wire by a drawing die.

5. A method for preparing a copper-tin alloy heating wire, characterized in that: The following steps are involved: Preparation of protective layer materials: Collect discarded rice straw and wash it with a cleaning device equipped with high-pressure water spray and rotating brush. The high-pressure water spray pressure is controlled at 5-8MPa and the rotating brush speed is 100-150 rpm. After washing, use a high-speed crusher to crush it into uniform fragments with a particle size range of 2-5 mm. Hydrolysis reaction: The crushed straw fragments are transferred to a reactor equipped with a precise temperature control system and a stirring device, and a sulfuric acid solution with a mass fraction of 8% is added. The mass ratio of straw fragments to sulfuric acid solution is 1:5-1:

8. The reaction temperature is precisely controlled at 85°C, the stirring device speed is 150-200 rpm, and the reaction time is 2.5 hours. Polymerization reaction: After the hydrolysis reaction is completed, cool to 55°C at a cooling rate of 5-8°C / min, add an appropriate amount of glutaraldehyde crosslinking agent, and add glutaraldehyde in an accurately calculated stoichiometric ratio of 1:2-1:3 to the active groups in the hydrolyzate. Stir at a low speed of 50-60 rpm for 3-4 hours in a constant temperature water bath environment; Mixing of nano-sized metal oxide particles: using a high-precision electronic balance with an accuracy of 0.0001 g, weigh nano-sized copper oxide and zinc oxide particles respectively in a copper oxide to zinc oxide mass ratio of 2.5:1, add them to the prepared natural polysaccharide matrix, and transfer to an ultrasonic dispersion device; Heating wire coating: Select the copper-tin alloy heating wire prepared in advance according to the heating performance requirements, pour the protective layer precursor solution into the corrosion-resistant polytetrafluoroethylene coating tank, and use the pulling method to coat it at a pulling speed of 1 cm / s. After coating twice, dry it in a low-temperature drying oven set at 45°C for 1.5 hours; Hollow channel formation: A hollow channel is formed inside the copper-tin alloy heating wire using a drawing die and a drawing process. The drawing die is made of cemented carbide material, and the shape and size accuracy of the internal channel is controlled within ±0.01mm; Antimicrobial filling: Tea tree essential oil is selected as the volatile antimicrobial agent and injected into the hollow channel through a high-precision microinjection pump. The injection pressure is controlled at 0.5-1MPa. The injection volume is calculated based on the volume of the hollow channel and the concentration of the tea tree essential oil. After the injection is completed, a water-resistant, temperature-resistant and well-adhesive epoxy resin sealant is used to seal both ends of the channel.

6. The method for preparing a copper-tin alloy heating wire according to claim 5, characterized in that: Before the protective layer raw material preparation step, the heating power demand of the sewage treatment equipment is analyzed, the actual working conditions of the sewage treatment equipment are simulated multiple times, and the resistance-temperature testing device is used to measure the resistance value and heating power of the heating wire under different copper-tin ratios to determine the ratio of copper to tin in the copper-tin alloy heating wire.

7. The method for preparing a copper-tin alloy heating wire according to claim 5, characterized in that: In the step of mixing the nano-sized metal oxide particles, the ultrasonic frequency is set to 40-60 kHz, the ultrasonic power is 250 W, and the ultrasonic dispersion time is 35 minutes.

8. The method for preparing a copper-tin alloy heating wire according to claim 5, characterized in that: During the drawing process of hollow channel formation, the drawing force and speed are monitored in real time by high-precision sensors, and the control system automatically adjusts the drawing parameters to control the drawing force to be stable at 10-15 kN and the drawing speed to be controlled at 0.5-1 m / min.